La mediación como procedimiento efectivo para la solución de los conflictos laborales individuales en la ciudad de Machala, año 2011. - Herrera Crespo, Oswaldo Alfredo (2012)
Circumstances that make possible the development of the thesis until a proposal for intervention in order that compliance of mediation as an effective procedure for settling individual disputes is required.